Harnessing caseinolytic proteases ClpP1P2 for next-generation antimycobacterial agents: Mechanisms, challenges and opportunities - Bonjorno, Andressa Franciélli [UNESP]; de Souza, Mateus Mello [UNESP]; Rodriguez Gini, Ana Luísa [UNESP]; Scarim, Cauê Benito [UNESP]; Dos Santos, Jean Leandro [UNESP] (Elsevier, 2025)
The caseinolytic protease (Clp) complex plays a fundamental role in protein homeostasis, ensuring the degradation of misfolded and damaged proteins in prokaryotic cells and eukaryotic organelles. Given its essential function, Clp has emerged as an attractive therapeutic target for bacterial infections, particularly for Mycobacterium tuberculosis (Mtb). The growing concern over antimicrobial resistance has prompted efforts to identify inhibitors and activators of ClpP1P2, the unique hetero-oligomeric protease in Mtb. This review explores the structural and functional characteristics of ClpP1P2 and its regulatory ATPase partners (ClpC1 and ClpX), detailing their role in bacterial viability and virulence. Advances in structural biology and proteomics have facilitated the development of novel inhibitors, including acyldepsipeptides (ADEPs), β-lactones, boronate derivatives, and pyrrole-based compounds, many of which exhibit promising antimicrobial activity. Additionally, the emergence of BacPROTAC technology, which leverages targeted protein degradation mechanisms to selectively deplete essential bacterial proteins, represents a groundbreaking strategy in tuberculosis drug discovery. Notably, several inhibitors have demonstrated significant efficacy in vitro and in vivo models, with selectivity towards Mtb ClpP1P2 over human proteasomes, reducing off-target effects. Despite these advances, challenges remain in optimizing compound selectivity, pharmacokinetic properties, and resistance profiles. This review highlights key discoveries in Clp-targeting strategies, emphasizing their potential to contribute to the development of next-generation antimycobacterial agents.